The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s00464-003-8216-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic exploration of common bile duct in difficult choledocholithiasis

Abstract: When ERCP is impossible or stone retrieval is incomplete, LECBD is the solution to difficult CBD stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 16 publications
0
48
1
3
Order By: Relevance
“…23 Studies evaluating complication rates in a operative-based approach for the management of obstructive choledochal stone disease report similar numbers, with complication rate ranging from 5% to 20%. 24,25 In the current study, patients initially admitted to a surgical service had significantly more complications during their index admission compared to those admitted to medicine. As these patients are also more likely to undergo an operative procedure-both cholecystectomy as a singlestaged approach as well as cholecystectomy with perioperative ERCP and/or ES-the greater complication rate for a patient admitted to a surgical team is not unexpected.…”
Section: Discussionmentioning
confidence: 93%
“…23 Studies evaluating complication rates in a operative-based approach for the management of obstructive choledochal stone disease report similar numbers, with complication rate ranging from 5% to 20%. 24,25 In the current study, patients initially admitted to a surgical service had significantly more complications during their index admission compared to those admitted to medicine. As these patients are also more likely to undergo an operative procedure-both cholecystectomy as a singlestaged approach as well as cholecystectomy with perioperative ERCP and/or ES-the greater complication rate for a patient admitted to a surgical team is not unexpected.…”
Section: Discussionmentioning
confidence: 93%
“…LCBDE is associated with successful stone clearance rates ranging from 85 to 95%, a morbidity rate of 4–16% and a mortality rate of around 0–2% [6,7]. Tai et al [34] reported that the clearance rate was 100%, and no recurrence was discovered during a mean follow-up period of 16 months. Moreover, LCBDE avoids the short-term (pancreatitis, bleeding and perforation), medium (cholangitis and recurrent stone formation) and long-term (bile duct malignancy) adverse effects of ES.…”
Section: Discussionmentioning
confidence: 99%
“…Schreurs et al showed 75%–84% patients undergoing ERCP/EST had no symptoms with up to 70-month followup [75]. Complications of ERCP include bleeding, duodenal perforation, cholangitis, pancreatitis, and bile duct injury [76]. Moreover, ERCP is not possible in 3% to 10% of all patients [77].…”
Section: Treatmentmentioning
confidence: 99%
“…Laparoscopic exploration is very effective for clearing difficult CBD stones. Tai et al reported that the clearance rate was 100%, and no recurrence was discovered during a mean followup period of 16 months [76]. Golipour et al showed LCBDE to be an effective procedure as the initial modality of management for acute gallstone cholangitis [92].…”
Section: Treatmentmentioning
confidence: 99%